Adaptive control of a hybrid electric vehicle - Ng, Alina Wen Ling (2014)
Hybrid Electric Vehicle (HEV) is a type of hybrid and electric vehicle which makes use of efficiency-improving technologies such as regenerative braking. These vehicles aim to reduce carbon emissions and wastage of energy and are increasingly popular in the world. While there is significant research on the energy management system within the vehicle, it is important that efforts to enhance driving safety though control systems are not neglected.